Selection of New Late-Season Mandarin Cultivars Based on Sensory Changes and Consumer Acceptance after Fruit Cold Storage - Tarancón, Paula; Giménez-Sanchís, Adrián; Aleza, Pablo; Besada, Cristina (MDPI, 2021)
Late-season mandarins are normally cold-stored to prolong the commercial season. Thus, it is necessary to investigate poststorage consumer acceptance to predict the potential success of new late-season mandarin varieties on the market. The aim of the present work was to evaluate consumer response to three new late-season cultivars preselected in the IVIA breeding programme (Omet, Matiz and Tri-703) after different cold storage periods. The three new cultivars were compared to commercial cultivars Orri, Nadorcott and Ortanique, all of which are widely available in stores. A multidisciplinary approach was used to determine the main changes during storage at 1 °C for up to one month: (1) analysis of physico-chemical parameters; (2) description of the sensory profile by semitrained assessors by the Free Choice Profile technique; (3) evaluation of consumer acceptability and purchase intention. Our results showed that the sensory changes that fruit underwent during storage depended on the variety; these changes allowed us to understand why consumer preferences varied during storage. Of the three new cultivars, two (Omet and Tri-703) showed the greatest potential for success. However, while Tri-703 can be stored for one month, Omet should not be stored longer than 15 days due to its susceptibility to manifest skin damage during storage. Of the commercial cultivars, internal Orri quality was keenly appreciated by consumers, while Ortanique was considered the most attractive variety. The multidisciplinary approach followed in this study proved to be a potent tool for selecting varieties that should be implemented in selection processes of breeding programmes